Lyding – ’n dringende aansporing: 1 Petrus 4:12–19 eksegeties nuut ondersoek - Douw G. Breed (In die Skriflig, 2024)
Suffering – an urgent exhortation: 1 Peter 4:12–19 exegetically re-examined. This article provides a new exegetical examination of the specific way Peter encourages the readers in 1 Peter 4:12–19 to remain faithful amid suffering. In this article, the grammatical-historical model, as practiced in the Reformed tradition, is followed in the exegesis. Peter exhorts the readers in 1 Peter 4:12–19 to be willing to suffer as Christians. He reinforces his exhortation by indicating that faithfulness amid suffering confirms the equipment of the Spirit and that faithfulness will result in joy when Christ’s glory is revealed. He warns that unfaithfulness will result in judgement.